2021
DOI: 10.1007/s11846-021-00498-1
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of matchmaking tools in coworking spaces: an extended perspective

Abstract: An extended technology acceptance model for matchmaking tools in coworking spaces is presented and tested among 92 German coworkers. Advancing previous research, hedonic and community-related aspects are integrated into a framework based on the extended unified theory of acceptance and use of technology (UTAUT2). Coworkers emphasize a matchmaking tool’s productivity aspects, which are positively moderated by their sense of community. Hedonic motivation (HM) and personal innovativeness contribute to usage inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…From a necessity perspective, fsQCA necessity analysis results showed that low perceived effort (i.e., EE) is a critical condition. This finding corroborates existing necessity results for technology acceptance models (Kopplin et al, 2021) and provides an important supplement to the existing insights into the role of effort. The majority of findings on technology acceptance uses structural equation modeling, which frequently identifies perceptions of low effort as exerting a small impact or being not significant as an independent variable (see, e.g., King & He, 2006).…”
Section: Theoretical Implicationssupporting
confidence: 88%
See 2 more Smart Citations
“…From a necessity perspective, fsQCA necessity analysis results showed that low perceived effort (i.e., EE) is a critical condition. This finding corroborates existing necessity results for technology acceptance models (Kopplin et al, 2021) and provides an important supplement to the existing insights into the role of effort. The majority of findings on technology acceptance uses structural equation modeling, which frequently identifies perceptions of low effort as exerting a small impact or being not significant as an independent variable (see, e.g., King & He, 2006).…”
Section: Theoretical Implicationssupporting
confidence: 88%
“…Surprisingly, PE was not a necessary condition for the male subset, contradicting existing work on necessary conditions in technology acceptance (Kopplin et al, 2021) but also questioning the variable's predominant position in technology acceptance frameworks. Commonly, multivariate analyses identify PE as a major factor (Im et al, 2011;Venkatesh et al, 2003;Zhou et al, 2010).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Despite its empirical robustness, ongoing research endeavors seek to refine and broaden the model to more comprehensively capture the intricacies of technology acceptance across diverse contexts (e.g. Addy et al, n.d.;Kopplin et al, 2022;Schomakers et al, 2022;Suo et al, 2022)…”
Section: Technology Acceptance Modelmentioning
confidence: 99%